Inтеgration as a basis of degree-oriented education in scientific-educational cluster - Evgeniy A. Korchagin; R. S. Safin (Высшее образование в России)
The article considers a curricula content and its role in an integration process within a scientific- educational cluster. The principles of multilevel education are defined. The interaction factors within the education levels and their influence on the integration process are reflected. The model of the education system based on the scientific-educational cluster is proposed. There is also discussed a problem of implementing the coherent curricula of participating educational institutions.